Photocatalytic decomposition of methanol over La/TiO2 materials - Kočí, Kamila; Troppová, Ivana; Edelmannová, Miroslava; Starostka, Jakub; Matějová, Lenka; Lang, Jaroslav; Reli, Martin; Drobná, Helena; Rokicińska, Anna; Kuśtrowski, Piotr; Čapek, Libor (Environmental science and pollution research international, 2018)
Lanthanum-modified TiO2 photocatalysts (0.2-1.5 wt% La) were investigated in the methanol decomposition in an aqueous solution. The photocatalysts were prepared by the common sol-gel method followed by calcination. The structural (X-ray diffraction, Raman, X-ray photoelectron spectroscopy), textural (N2 physisorption), and optical properties (diffuse reflectance spectroscopy, photoelectrochemical measurements) of all synthetized nanomaterials were correlated with photocatalytic activity. Both pure TiO2 and La-doped TiO2 photocatalysts proved higher yields of hydrogen in comparison to photolysis. The photocatalyst with optimal amount of lanthanum (0.2 wt% La) showed almost two times higher amount of hydrogen produced at the same time as in the presence of pure TiO2. The photocatalytic activity increased with both increasing photocurrent response and decreasing amount of lattice and surface O species. It has been shown that both direct and indirect mechanisms of methanol photocatalytic oxidation participate in the production of hydrogen. Both direct and indirect mechanisms take part in the formation of hydrogen.
Keywords: fotoelektronová spektroskopie; methanol; Catalysis; vodík; chemické látky znečišťující vodu; Photoelectron Spectroscopy; katalýza; Water Pollutants, Chemical; lanthan; Methanol; Titanium; fotochemické procesy; titan; Hydrogen; X-Ray Diffraction; difrakce rentgenového záření; Photochemical Processes; fotolýza; Photolysis; Lanthanum